Giant splenic abscess caused by Salmonella enterica. Issue 4 (19th March 2021) - Mulita, Francesk; Liolis, Elias; Tchabashvili, Levan; Seretis, Fotios; Iliopoulos, Fotios; Drakos, Nikolas; Maroulis, Ioannis; Vailas, Michail
Abstract: Splenectomy is the gold standard for treating a splenic abscess, when percutaneous drainage fails or is less likely to be successful. Abstract : Splenectomy is the gold standard for treating a splenic abscess, when percutaneous drainage fails or is less likely to be successful.